Evaluation of the nutritional value of Leucaena leucophala leaf meal hydrolyzed by sheep rumen liquor enzyme extract on the growth performance of Nile tilapia (Oreochromis niloticus) - Fitriliyani, Indira (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
This experiment was conducted to evaluatee the nutritional value of Leucaena leucocephala leaf meal (LLM) with supplementation of sheep rumen liquor crude enzyme on the growth of Nile tilapia. Fish were fed isonitrogenous (± 32% crude protein and C/P ± 9.25 ccal/kg) diets for 50 days. Six diets were formulated to contain hydrolyzed LLM at level 10%, 15%, 20%, 25% and 30% (Diet A, B, C, D and E respectively) and one diet acting as a control (Diet K, 0% LLM). All diets were isonitrogenous and isoenergy. A seven week feeding trial was carried out on triplicate groups of eight fish (9.38 ± 0.41) in 18 aquarium with a recirculating system. Fish were fed twice daily at satiation. Results of the present study indicated that the fish fed diet contained 0%, 10% and 15% of lamtoro leaf meal had significantly higher in specific growth rate (SGR) than other groups (p